Pulmonary Procoagulant and Innate Immune Responses in Critically Ill COVID-19 Patients - Nossent, Esther J.; Schuurman, Alex R.; Reijnders, Tom D.Y.; Saris, Anno; Jongerius, Ilse; Blok, Siebe G.; de Vries, Heder; Duitman, JanWillem; Vonk Noordegraaf, Anton; Meijboom, Lilian J.; Lutter, René; Heunks, Leo; et al. (Frontiers in Immunology, 2021)
Rationale: Systemic activation of procoagulant and inflammatory mechanisms has been implicated in the pathogenesis of COVID-19. Knowledge of activation of these host response pathways in the lung compartment of COVID-19 patients is limited. Objectives: To evaluate local and systemic activation of coagulation and interconnected inflammatory responses in critically ill COVID-19 patients with persistent acute respiratory distress syndrome. Methods: Paired bronchoalveolar lavage fluid and plasma samples were obtained from 17 patients with COVID-19 related persistent acute respiratory distress syndrome (mechanical ventilation > 7 days) 1 and 2 weeks after start mechanical ventilation and compared with 8 healthy controls. Thirty-four host response biomarkers stratified into five functional domains (coagulation, complement system, cytokines, chemokines and growth factors) were measured. Measurements and Main Results: In all patients, all functional domains were activated, especially in the bronchoalveolar compartment, with significant increased levels of D-dimers, thrombin-antithrombin complexes, soluble tissue factor, C1-inhibitor antigen and activity levels, tissue type plasminogen activator, plasminogen activator inhibitor type I, soluble CD40 ligand and soluble P-selectin (coagulation), next to activation of C3bc and C4bc (complement) and multiple interrelated cytokines, chemokines and growth factors. In 10 patients in whom follow-up samples were obtained between 3 and 4 weeks after start mechanical ventilation many bronchoalveolar and plasma host response biomarkers had declined. Conclusions: Critically ill, ventilated patients with COVID-19 show strong responses relating to coagulation, the complement system, cytokines, chemokines and growth factors in the bronchoalveolar compartment. These results suggest a local pulmonary rather than a systemic procoagulant and inflammatory “storm” in severe COVID-19.